1998
DOI: 10.1111/j.1479-828x.1998.tb03002.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Resistance to Activated Protein C in The Course of Pregnancy and Prevalence of Factor V Mutation

Abstract: The purpose of this study was to examine the changes in activated protein C (APC) anticoagulant activity during pregnancy and determine whether changes in APC could contribute to thrombosis in the placental bed in preeclampsia. We measured APC anticoagulant activity in 150 women with a normal pregnancy and 50 women with preeclampsia. There was a significant reduction in the mean APC sensitivity ratio (APC-SR) during pregnancy (p<0.001). APC resistance in preeclampsia was significantly higher than in normal pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…The overall prevalence of Factor V Leiden in Caucasians is cited as approximately 5%–6% but there is considerable racial and geographic variation 2,20 . Two previous Australian studies have reported prevalence rates of 0.07% 21 and 3.6% 22 for the Factor V Leiden, both figures considerably lower than that found in the present study. Heterogeneity of the Factor V Leiden within populations is evident in studies from the Netherlands 4,23 , Germany 9,24 and the UK 19 .…”
Section: Risk Of Bias In the Selection Of Normal Pregnancy Controlscontrasting
confidence: 80%
“…The overall prevalence of Factor V Leiden in Caucasians is cited as approximately 5%–6% but there is considerable racial and geographic variation 2,20 . Two previous Australian studies have reported prevalence rates of 0.07% 21 and 3.6% 22 for the Factor V Leiden, both figures considerably lower than that found in the present study. Heterogeneity of the Factor V Leiden within populations is evident in studies from the Netherlands 4,23 , Germany 9,24 and the UK 19 .…”
Section: Risk Of Bias In the Selection Of Normal Pregnancy Controlscontrasting
confidence: 80%
“…Table 2 summarizes the analysis of 23 studies involving 3131 patients and 4036 controls that assessed the association between FVL and all preeclampsia [7][10], [19][21], [23], [26], [27], [29], [30], [32], [33], [35], [41], [42], [44][47], [50], [51]. Meta-analysis revealed a significant association between FVL and preeclampsia (pooled OR = 1.60, 95% CI 1.28–2.00, p  = 0.251, I 2  = 15.5%) when a fixed model was applied (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Severe preeclampsia was determined if one or more of the following features were present: blood pressure ≥160/110 mmHg; proteinuria >3+; oliguria; seizures; visual disturbances; headache; HELLP (hemolysis, elevated liver enzymes, and low platelets); right upper-quadrant pain; and thrombocytopenia. The remaining studies [7], [8], [32][52] used modified but relatively compatible diagnostic criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure , 477 articles were filtered after reviewing based on the exclusion criteria, including the title or abstract relevance to our study, is it possible to get full‐text, and does it exist detailed data. Finally, a total of 50 case–control studies(Table ) involving 6041 cases and 8364 controls were ultimately included in our meta‐analysis. All data were obtained from existing studies, with populations from Europe, the Middle East, North America, Latin America, Asia or Australia.…”
Section: Resultsmentioning
confidence: 99%